2012
DOI: 10.1007/10_2012_143
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Approaches in the Identification of Molecular Signatures of Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are undifferentiated, multi-potent stem cells with the ability to renew. They can differentiate into many types of terminal cells, such as osteoblasts, chondrocytes, adipocytes, myocytes, and neurons. These cells have been applied in tissue engineering as the main cell type to regenerate new tissues. However, a number of issues remain concerning the use of MSCs, such as cell surface markers, the determining factors responsible for their differentiation to terminal cells, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…[32][33][34][35][36] All these MSCs have similar molecular markers with positive expression of mesenchymal markers (CD90, CD29, CD44, and CD105) and lack of CD34, CD45, CD11b, and HLA-DR. 36,37 MSCs from adipose tissue (ASCs) are extensively studied to substitute BMSCs with several obvious advantages. First, the adipose tissues are easier to obtain than bone marrow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35][36] All these MSCs have similar molecular markers with positive expression of mesenchymal markers (CD90, CD29, CD44, and CD105) and lack of CD34, CD45, CD11b, and HLA-DR. 36,37 MSCs from adipose tissue (ASCs) are extensively studied to substitute BMSCs with several obvious advantages. First, the adipose tissues are easier to obtain than bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…139 MSCs may also differentiate into other cells types such as neurons, cardiomyocytes, hepatocytes, and pancreatic betacells. 35 However, the role of PI3K/Akt pathway in the differentiation of these cells has not been studied well. Further exploration of the pathway may help to promote the potential use of MSCs in the regeneration of these cells.…”
mentioning
confidence: 99%
“…Metabolic reprogramming of differentiating MSCs is accomplished in part by post-translational modification of proteins required for MSC maintenance and differentiation (Li et al, 2011;Xiao and Chen, 2012;Jeon et al, 2016). Post-translational modification in the mitochondria and proteinprotein interactions that modify diverse mitochondrial functions are impacted by cellular demand, nutrient availability, and redox conditions.…”
Section: Sirtuins In Metabolic Reprogrammingmentioning
confidence: 99%
“…Sirtuins known as histone deacetylases are relevant to the control of longevity, energy metabolism, and cell development in mammals ( 12 ). It was reported that sirtuins can affect the fate of stem cells through deacetylation of histone and non-histone proteins involved in gene expression ( 13 ). Recent studies demonstrated that the deficiency of Sirtuins influences reprogramming efficiency ( 14 ) and contributes to genomic instability, which as we noted, is an important issue in the cell reprogramming process ( 15 ).…”
Section: Introductionmentioning
confidence: 99%